The law of large-scale claims: product liabilty, mass torts, and complex litigation in Canada - Cassels, Jamie (Irwin Law, 2005)
On its simplest level, the purpose of this book is to explain the legal rules applicable to cases of large scale claims, typically in "product liability" and "mass torts." The book builds on a recognition that there is a field of practice--and, increasingly, of legal study--which demands a working comprehension of the way in which a number of apparently diverse fields of practice interact in the modern courtroom. These practice areas include, but are not limited to, product liability, torts, corporation law, evidence, conflict of laws, class actions, and the law of remedies. Large scale claims have generated significant changes to both substantive and procedural rules as courts struggle to reconcile modern models of production and consumption with the requirements of justice in the enforcement of private and public obligations. It is this struggle which The Law of Large-Scale Claims addresses.